Bone-peg grafting for osteochondritis dissecans of the elbow - Oka, Y. (Springer-Verlag, 1999)
In the treatment of osteochondritis dissecans involving the elbow, we have used a bone-peg graft taken from the proximal part of the ulna and inserted into the defect. Thirty-two patients were followed from 2 to 10.5 years. The graft was utilised in 20 elbows, and 6 of these also had concomitant removal of a loose body. Another 6 elbows had removal of a loose body only. Ten elbows were treated conservatively in 5 of these the outcome was unsatisfactory, including 4 in which a bone-peg graft was later necessary. The bone-peg graft gave the best short-term results. Bony union of the dissecans site and reconstitution of subchondral bone required an average of 6.5 months. In 15 patients followed for a minimum of 5 years, the bone-peg graft was effective in limiting the development of osteoarthritis. Bone-peg grafting is a reliable method for treating osteochondritis dissecans of the elbow.